The Influence of E-Wom Quality and Trust on Purchase Decisions with The Mediating Role of E-Wom Adoption - Pagi, Nurani Embun; Praswati, Aflit Nuryulia (Universitas Muhammadiyah Surakarta, 2025)
Technological advances have changed consumer behavior, making them more active in searching for and comparing product information online through reviews and digital media before deciding to make a purchase. This study aims to analyze the influence of e-WOM quality and trust on purchase decisions mediated by e-WOM adoption among social media and marketplace users. The research method used a quantitative approach with Structural Equation Modeling-Partial Least Squares (SEM-PLS) analysis and involved 170 respondents. The results show that e-WOM Quality and Trust have a positive and significant effect on e-WOM Adoption and Purchase Decision. Additionally, e-WOM Adoption mediates the relationship between e-WOM Quality and Trust on Purchase Decision. This study confirms that information quality and consumer trust are important factors that drive information adoption, leading to purchase decisions on digital platforms.